Brasil: política e cidadania - Pironi, Rodrigo Derobio [UNESP]; Assumpção, Ana Júlia [UNESP]; Barroti, Carolina [UNESP]; Cardillo, César Augusto [UNESP]; Duarte, Cristiano Parra [UNESP]; Stern, Danielle Cristine [UNESP]; Monteiro, Emmanuel Pinto [UNESP]; Marques, Fernanda Castro [UNESP]; Zanotti, Gabriela [UNESP]; Fredini, João [UNESP]; Andrade, João Vitor [UNESP]; Silva, Juliane de Aguiar [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
The present work reports a project of the “Pet Administração Pública” in public schools with high school students in the city of Araraquara. The project aims at an interaction with students from the perspective politics and citizen of our country, by offering them educational booklets and forms. The first year of implementation of the project was in 2009 and since then it has been improving every year.

O presente trabalho relata um dos projetos de extensão do Pet Administração Pública, atuando em escolas públicas junto aos alunos de ensino médio no município de Araraquara. O projeto visa uma interação com os alunos sob a ótica política e cidadã de nosso país, oferecendo-lhes cartilhas didáticas e formulários. O primeiro ano de aplicação do projeto foi em 2009 e desde então ele vem se aprimorando anualmente.
Keywords: Democracy; Polity; Social participation; Democracia; Política; Participação social